Curras: an annotated corpus for the Palestinian Arabic dialect. - Jarrar, Mustafa; Habash, Nizar; Alrimawi, Faeq; Akra, Diyam; Zalmout, Nasser (Language Resources & Evaluation, 2017)
In this article we present Curras, the first morphologically annotated corpus of the Palestinian Arabic dialect. Palestinian Arabic is one of the many primarily spoken dialects of the Arabic language. Arabic dialects are generally under-resourced compared to Modern Standard Arabic, the primarily written and official form of Arabic. We start in the article with a background description that situates Palestinian Arabic linguistically and historically and compares it to Modern Standard Arabic and Egyptian Arabic in terms of phonological, morphological, orthographic, and lexical variations. We then describe the methodology we developed to collect Palestinian Arabic text to guarantee a variety of representative domains and genres. We also discuss the annotation process we used, which extended previous efforts for annotation guideline development, and utilized existing automatic annotation solutions for Standard Arabic and Egyptian Arabic. The annotation guidelines and annotation meta-data are described in detail. The Curras Palestinian Arabic corpus consists of more than 56 K tokens, which are annotated with rich morphological and lexical features. The inter-annotator agreement results indicate a high degree of consistency.